LAGU DANGDUT POPULER : ANTARA EKSPLOITASI DAN EKSHIBISI TUBUH DAN SEKSUALITAS PEREMPUAN - Qibthia, Maria (Fakultas Komunikasi, Sastra, dan Bahasa, 2013)
Thispaperdiscusses therepresentations ofwomen'sbodiesandsexualities whicharemediatedinthe lyrics ofdangdut popular, sothis essaywill bewrittenby usingfeminismperspective wheremediasuchas songsasthe sources.By analyzing three popular dangdut song lyrics, there are two assumptions about how wom-en's bodies and sexuality represented and constructed by the media. The first assumption, that the lyrics of the song that contains elements of female sexuali-ty can be a trigger to the exploitation of women. However, the second assump-tion states that the dangdut song can be regarded as exhibition of women?s bo-dies and sexuality.